Evaluation of the Response of Some Wheat (Triticum Spp.) Varieties for Salinity Stress Tolerance Using Growth Parameters in-vitro (Damascus University Journal of agriculture sciences, 2021)
The experiment was conducted in order to study the effect of Nacl-induced salt stress on some growth traits in eight wheat varieties (Triticum Spp.) grown in-vitro. Salt stress was imposed by adding different concentrations of NaCl to the culture medium (0, 50, 100 and 150 mM), which are equal to -0.2, -0.4, -0.55 and -0.73 MPa on the osmotic potential basis. Results revealed a genetic variability in the response of the investigated varieties for salt stress based on the studied parameters. Progressive reduction in the studied parameters occurred as salt stress increased compared with control. Grouping all the varieties by cluster analysis, based on the growth parameters response to salt stress showed three distinct groups: The Salt stress tolerant group, which included four varieties (Bohouth7, Bohouth11, Guolan2 and Bohouth8), the moderately salt stress tolerant group, included two varieties (Sham3 and Doma4) and the salt stress susceptible group, included two varieties (Sham10 and Doma1). These results indicate the possibility of using the in-vitro screening to evaluate the genetic variability of wheat varieties for Nacl-induced salt stress tolerance.